Stapler Haemorrhoidopexy for the Management of Haemorrhoids in Sudan (Global Journal of Medical Research, 2014)
Background : Haemorrhoidectomy is a commonest anal surgical procedure which is usually associated with post operative pain, Stapled Haemorrhoidopexy (SH) is a new alternative to conventional haemorrhoidectomy (CH). It was first described by Dr. Antonio Longo, in 1998 and since then it has been widely adopted, and can be used in the management of 2nd, 3rd and 4th degree hemorrhoids. Objective : To study (SH) in Sudan and to evaluate its effectiveness in the treatment of haemorrhoids. Patients and Methods : It is a retro-prospective descriptive study. Conducted at multicentres (7 hospitals) in the period from 2009 January to 2013 August. It included all Cases of 2nd, 3rd and 4th degree haemorrhoids underwent (SH) procedure. Data regarding the clinical presentation, duration of the surgery, postoperative complications, duration of hospital stay and period of retaining to normality were reviewed and analyzed using (SPSS) .The mean follow up duration was 28 months. Results : The study included 100 patients, 80 men and 20 women (23 – 85) years with mean age (42.2years ± SD 14.2). Male to female ratio was 4:1.This male gender preponderance was found to be statistically significant (P value 0.007) The most frequent symptoms either alone or in combination with other symptoms were pain 83%, swelling/prolapse 57% or bleeding 64%. Third degree haemorrhoid represents 56% of the patients, 4th degree haemorrhoid in 34% and 10% had second degree who were not respond to conservative management. The mean duration of surgery was (35.6 minutes ± SD 19.4) and ranged between (15 -120) min. The immediate post-operative pain was experience by 68 patients 68% and assessed by Visual Analogue Scale, mild to moderate pain in 53% of the patients and the pain fade by day three post-operative in 89%. Minor post-operative complications were seen in 66 patients. In more than half of them it was pain with or without defecation 45%, bleeding in 8%, urine retention in 6%. During the follow up whic
Keywords: stapled haemorrhoidopexy; haemorrhoi ds; haemorrhoidectomy